IgG antibodies anti-LcrV of Yersinia pestis: inconsistent responses in confirmed plague patients from Madagascar - Olifara Herinirina Andriatefy; Anjanirina Rahantamalala; Matthieu Schoenhals; Robin Shattock; Nicola J. Walker; Ethel Diane Williamson; Minoarisoa Rajerison; Voahangy Andrianaivoarimanana (BMC Research Notes)
Abstract Objective Plague (Yersinia pestis infection) is a flea-borne zoonotic disease mainly affecting African countries, with most human cases reported from Madagascar and the Democratic Republic of Congo. Although curable, plague can be fatal without prompt treatment, highlighting the importance of reliable diagnostics. Current tests include bacteriological culture, PCR, and anti-F1 ELISA, however the anti-F1 serology has limitations due to the existence of F1-negative virulent strains. To address this, we developed a serological test detecting IgG antibodies against LcrV or V antigen, the main virulence factor of Y. pestis and further evaluated the developed test on clinical samples. Results V antigen was produced from the culture of V-pGEX-6P-2 clones and purified as GST-LcrV, which was functional for ELISA plate coating. The developed anti-V ELISA showed 60% sensitivity and 93.3% specificity when tested on confirmed plague patients’ serum samples from Madagascar. However, evaluation on convalescent sera collected from Day 1 to Month 3 post-infection revealed inconsistent anti-V antibody production. This suggests the anti-V ELISA is best used as a complementary test for plague diagnosis and during outbreak investigations. In addition, this study provides valuable insight into the humoral response diversity following Y. pestis infection, representing crucial information for plague vaccine development.